FORMULASI DAN EVALUASI SEDIAAN TABLET HISAP DARI BAHAN EKSTRAK BUNGA TELANG (Clitoria ternatea L.) UNTUK MENGERCERKAN DAHAK - Govan Hanif Sasongko; Jupita; Astrid Vanessa Putri Erwanda; Pangestika Widyasrini; Tiara Alfiaa’yuni (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Butterfly pea flowers are used as eye medicine, phlegm thinner, and food coloring, but they have pharmacological benefits as antioxidants, antibacterials, antiparasitics, antidiabetics, anti-inflammatory, and anticancer. Phlegm will usually accumulate until it becomes thick and becomes difficult to expel. Diseases of the respiratory system that are most often suffered by children include acute respiratory infections (ISPA). The aim of this research is to find out the correct formulation and method of making lozenges according to CPOB, then evaluate the physical preparation to ensure the quality of the preparation. The butterfly pea flower extract lozenges were subjected to phytochemical testing, granule evaluation, and lozenge evaluation. yield 7.2%, solvent-free test does not smell of ester, which means the ethanol extract of butterfly pea flower is positive for ethanol solvent-free, flavonoid test produces a red color, which means it contains flavonoids. Physical properties test of the tablet requires results, namely, flow rate 7 seconds, angle of repose 30°, compatibility 6%, humidity 2.30%, organoleptic has a light gray color, sweet smell typical of butterfly pea flower extract, slightly sweet taste, round shape, weight uniformity 0.956%, size uniformity 1, disintegration time 7 minutes, friability 0.28%.